Program Pemuda Peduli Kesehatan Mental Melalui Pembentukan Konselor Sebaya di Desa Oenoni 2 - Maryati A. Barimbing; Fepyani Thresna Feoh; Jhon Enstein (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Mental disorders can occur at adults because the pressures due to physical, mental, social, economic. It is very unfortunate if family and peers don’t understand an individual's condition, and ignore it. Adults need support from other people, including peers. Community service include 5 stages, socialization, training, application of technology, mentoring and evaluation and sustainability. This activity was carried out by 50 young people in Oenoni 2 village with used pocket books, leaflets, banners, power point. Before and after socialization and training, youth knowledge was measured using a questionnaire. During training, youth practice how to become counselors. Youth were also divided into small groups to conduct FGD to build awareness about mental health. The results showed that there was an increase in knowledge from 5 to 9, also an increase in youth skills and awareness. Youth of Oenoni 2 village can disseminate information about mental health and become peer counselors